2009
DOI: 10.1007/s00586-009-0976-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Wallis implant reduce adjacent segment degeneration above lumbosacral instrumented fusion?

Abstract: Delayed complications following lumbar spine fusion may occur amongst which is adjacent segment degeneration (ASD). Although interspinous implants have been successfully used in spinal stenosis to authors' knowledge such implants have not been previously used to reduce ASD in instrumented lumbar fusion. This prospective controlled study was designed to investigate if the implantation of an interspinous implant cephalad to short lumbar and lumbosacral instrumented fusion could eliminate the incidence of ASD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 62 publications
1
65
0
5
Order By: Relevance
“…Results of the current study confirm its effect on motion, and extension was the most affected. A study by Korovessis et al found that the Wallis implant could change the natural history of disc degeneration, with significant reduction of clinical and radiological incidence of ASD at 5-year follow-up [26]. The procedure to implant the Wallis is safe and associated with low morbidity, but requires the resection of the supraspinous and interspinous ligaments [13].…”
Section: Discussionmentioning
confidence: 99%
“…Results of the current study confirm its effect on motion, and extension was the most affected. A study by Korovessis et al found that the Wallis implant could change the natural history of disc degeneration, with significant reduction of clinical and radiological incidence of ASD at 5-year follow-up [26]. The procedure to implant the Wallis is safe and associated with low morbidity, but requires the resection of the supraspinous and interspinous ligaments [13].…”
Section: Discussionmentioning
confidence: 99%
“…inclusion criteria (2,3,6,(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(26)(27)(28)(29)(30)33,34,36,37,(41)(42)(43)(45)(46)(47) (Figure 1). For the possible duplicate studies (31&40,14&23,13&15), only the data from the trial with the longest follow-up were used for estimating the incidence of ASD.…”
Section: Zhou Zj Et Al: Can Posterior Dynamic Stabilization Reduce Tmentioning
confidence: 99%
“…Among the eight articles that used PDS devices as adjuncts to fusion, PDS were implanted adjacent to fusion in four articles (12,22,27,33), as a component part of hybrid fusion in three (20,21,28), and both in one (41) ( Table III). Three trials compared the incidence of ASDeg/ASDis between the sole fusion and fusion plus adjacent PDS (12,22,33).…”
Section: Zhou Zj Et Al: Can Posterior Dynamic Stabilization Reduce Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The intention is to alter the load bearing pattern of the motion segment, as well as to control any abnormal motion at the segment. The hypothesis behind dynamic stabilization is that control of abnormal motions and more physiological load transmission would relieve pain, and prevent adjacent segment degeneration because it permits a certain degree of motion in the fixed segment (7).…”
Section: Introductionmentioning
confidence: 99%